The Histone Methyltransferase DOT1L Promotes Neuroblastoma by Regulating Gene Transcription - Wong, Matthew; Tee, Andrew E.L.; Milazzo, Giorgio; Bell, Jessica L.; Poulos, Rebecca C.; Atmadibrata, Bernard; Sun, Yuting; Jing, Duohui; Ho, Nicholas; Ling, Dora; Liu, Pei Yan; Zhang, Xu Dong; et al. (Cancer research (Chicago, Ill.), 2017)
Myc oncoproteins exert tumorigenic effects by regulating expression of target oncogenes. Histone H3 lysine 79 (H3K79) methylation at Myc-responsive elements of target gene promoters is a strict prerequisite for Myc-induced transcriptional activation, and DOT1L is the only known histone methyltransferase that catalyzes H3K79 methylation. Here, we show that N-Myc upregulates DOT1L mRNA and protein expression by binding to the DOT1L gene promoter. shRNA-mediated depletion of DOT1L reduced mRNA and protein expression of N-Myc target genes ODC1 and E2F2. DOT1L bound to the Myc Box II domain of N-Myc protein, and knockdown of DOT1L reduced histone H3K79 methylation and N-Myc protein binding at the ODC1 and E2F2 gene promoters and reduced neuroblastoma cell proliferation. Treatment with the small-molecule DOT1L inhibitor SGC0946 reduced H3K79 methylation and proliferation of MYCN gene–amplified neuroblastoma cells. In mice xenografts of neuroblastoma cells stably expressing doxycycline-inducible DOT1L shRNA, ablating DOT1L expression with doxycycline significantly reduced ODC1 and E2F2 expression, reduced tumor progression, and improved overall survival. In addition, high levels of DOT1L gene expression in human neuroblastoma tissues correlated with high levels of MYCN, ODC1, and E2F2 gene expression and independently correlated with poor patient survival. Taken together, our results identify DOT1L as a novel cofactor in N-Myc–mediated transcriptional activation of target genes and neuroblastoma oncogenesis. Furthermore, they characterize DOT1L inhibitors as novel anticancer agents against MYCN-amplified neuroblastoma. Cancer Res; 77(9); 2522–33. ©2017 AACR.